Handbook of Adoption: Implications for Researchers,Practitioners, and Families 2007
DOI: 10.4135/9781412976633.n1
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Seal: Taking Adoption Issues to the Academicand Professional Communities

Abstract: Adoptions have taken place throughout history in various forms, where children end up being raised at some point in their lives by people other than their birth parents. It was even present at the very beginning of the birth of the United States as a nation. In fact, many adopted triad members have led notable and illustrious lives. Well-known and admired adoptees include leaders (e.g., Catherine I, Crazy Horse, John Hancock, William Jefferson Clinton), artists (e.g., Gian Giacomo Caprotti), performers (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…For example, a UK study that analysed social work assessments found that gay men wishing to become an adoptive or foster parent sometimes faced discriminatory and homophobic attitudes ( Hicks, 2005 ). Seen through an intersectional lens ( Collins, 1998 ; Bowleg, 2008 ), the present findings reveal how various aspects of fathers’ identities, such as relationship status and gender, appeared to have an additive effect in fathers’ perceptions of others’ views of their ability to become an adoptive parent, mirroring Boyer’s (2007) finding that same-gender male couples experienced ‘double stigma’ when adopting. Further, the findings indicate that despite a large body of research demonstrating that family structure is less influential than the quality of family relationships for children’s psychological adjustment ( Golombok, 2020 ), single fathers still experience prejudice ( Carone et al , 2021a ).…”
Section: Discussionsupporting
confidence: 58%
“…For example, a UK study that analysed social work assessments found that gay men wishing to become an adoptive or foster parent sometimes faced discriminatory and homophobic attitudes ( Hicks, 2005 ). Seen through an intersectional lens ( Collins, 1998 ; Bowleg, 2008 ), the present findings reveal how various aspects of fathers’ identities, such as relationship status and gender, appeared to have an additive effect in fathers’ perceptions of others’ views of their ability to become an adoptive parent, mirroring Boyer’s (2007) finding that same-gender male couples experienced ‘double stigma’ when adopting. Further, the findings indicate that despite a large body of research demonstrating that family structure is less influential than the quality of family relationships for children’s psychological adjustment ( Golombok, 2020 ), single fathers still experience prejudice ( Carone et al , 2021a ).…”
Section: Discussionsupporting
confidence: 58%
“…By focusing on adoptive fathers, this study sheds further light on the experience of parenting outside the realm of biological kinship. Like gay and lesbian families, adoptive families and adopted children are often stigmatized and viewed as a second tier of families (Javier, Baden, Biafora, Camacho‐Gingerich, & Henderson, ). Questions posed to adopted children like “Who is your real mother?” suggest that an adoptive family is somehow not legitimate and that relationships between adoptive parents and their children are inferior.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the millions of children who are currently in adoptive families globally, researchers agree that there is very little information or training to support education professionals who currently work with these children and their families at school (Baker, 2013;Donalds, 2012;Javier, Baden, Biafora, & Camacho-Gingerich, 2007;Taymans et al, 2008). Limited empirical data has been gathered by Australian researchers due to the legal family status afforded adoptees after they join their adoptive families and to changing government priorities regarding child welfare and safety.…”
Section: Chapter Summary and Implicationsmentioning
confidence: 99%